ANALISIS PRODUK PEGADAIAN SYARIAH DI KANTOR WILAYAH II PEKANBARU PROVINSI RIAU - Ali, Sri Indriyani; Baihaqi, Ahmad (STAI Sulthan Syarif Hasyim, 2024)
Sharia pawnshops are a solution that emerged amidst public anxiety regarding fraudulent practices disguised as services, and also against the background of reduced public trust in community institutions that are oriented towards offering services. The development of sharia-based products is increasingly widespread in Indonesia, no except pawnshops. The pawnshop company issues shariabased products called sharia pawnshops. Basically, sharia-based products have characteristics such as not charging interest in various forms due to usury, establishing money as a medium of exchange, not as a commodity. Traded, and conduct business to obtain compensation for services and or profit sharing. At the Sharia Pegadaian in the Pekanbaru Region II office, Riau province, they have 3 products that they offer to the public, namely gold installment products (gold investment, gold savings, gold gathering), Sharia KUR (People's Business Credit), financing the Haj portion (Arrum Haji). With a variety of products on offer This Sharia pawnshop is very helpful to the community, especially the lower middle class who need loans.